Black Movement in Brazil: approval of Law no. 10,639/2003 and education for ethnic-racial relations (Práxis Educativa, 2022)
In this article, the bibliographic research is used to investigate the strengthening of the Brazilian Black Movement after the construction and implementation of Law no. 10,639/2003. It is analyzed what actions have historically boosted the struggle for ethnic-racial relations in Brazil and to what extent this Law, as a public policy, has a dialog with the Movement in the construction of anti-racist education. This is a qualitative research, with an exploratory and analytical approach, being necessary to consider in this study the social, political, historical and cultural characteristics as essential elements in the formulation of the documents that are analyzed. The theoretical foundation of the article is based on Brutsher and Scocuglia (2017), Domingues (2007), Freire (1987), Gohn (1997), Gonçalves and Silva (2000), Lins (2016), Pereira (2017) and Rocha (2006) and on official documents that regulated Law no. 10,639/2003 (BRASIL, 2003, 2004b, 2013, 2019). The results point out that the history of the Brazilian Black Movement is marked by advances and ruptures that culminated in the implementation of Law no 10,639/2003.Keywords: Brazilian Black Movement. Anti-racist education. Law no. 10,639/2003.